RATTUS (Rat Thoracic Ultrasound): diagnosis of pneumothorax in pet rats - Piskovská, A.; Kraszewska, K.; Hauptman, K.; Chloupek, J.; Linhart, P.; Jekl, V. (Frontiers in Veterinary Science, 2024)
IntroductionRat thoracic ultrasound (RATTUS) is a non-invasive, easy-to-perform method for the evaluation of the pleural space and lungs in pet rats. The aim of the article is to present species-specific differences in the sonographic diagnosis of pneumothorax (PTX) in pet rats.MethodsIn total, 158 client-owned pet rats were examined during the period from July 2023 to January 2024. PTX was diagnosed in 20 of the examined rats (13.25%, the age of the animals ranged from 2 months to 32 months (19.08 ± 6.93 months; mean ± SD) and their body weight ranged from 97 g to 885 g (461.27 ± 138.97 g; mean ± SD). Radiographic confirmation of PTX was performed in all these 20 rats, in the control group radiography was used to confirm that PTX was not present.ResultsThe lung point and the barcode sign was found in 7/20 animals with sensitivity of 33.3% (95% CI, 0.16–0.59) and specificity of 100% (95% CI, 0.97–1.0). The abnormal curtain sign was found in 19/20 of animals with the sensitivity of 95% (95% CI, 0.73–0.99.7) and the specificity of 89% (95% CI, 0.82–0.93). The abnormalities in the substernal access were in 17/20 of animals with the sensitivity of 85% (95% CI, 0.61–0.96) and the specificity of 71% (95% CI, 0.62–0.78).DiscussionIn conclusion, RATTUS is a non-invasive method for the diagnosis of PTX in rats. Lung point and barcode sign are specific but not easily diagnosed signs. The curtain sign in RATTUS is not specific for PTX, as there are e.g. geriatric rats (rats older than 1,5 years) in which the abnormal curtain sign is visible without the presence of PTX. The presence of moderate to severe PTX can be assessed by the substernal approach based on the presence of cardiac displacement toward the collapsed lung lobe, and on evaluation of the lung inflation symmetry. This sign is not specific for PTX but in conjunction with other ultrasonic signs described makes the RATTUS a feasible tool for PTX diagnosis in rats.